Measurement of Wakarorosku Natural Program Implementation Impact PT. KPC with Social Return on Investment Approach - Dhani Aryanto; Nani Rohaeni Rohaeni; Naufal Fadhil (Ridwan Institute, 2022)
The variety of tribes in East Kalimantan also has various forms of motifs and carving patterns. Efforts to continue to preserve the local arts and culture of East Kalimantan, especially the Dayak Basap tribe, require the support of every stage holder/stakeholder. One of the efforts that have been implemented is community empowerment towards the introduction of batik culture and the ability to generate other income from batik activities. The Empowerment Program implemented by PT KPC is an investment. As a consequence of an investment, it is important for investors to know the results of the investment. In practice, many companies have not carried out an assessment process for the social investments that have been made, especially in terms of indirect results (outcomes) and related to the resulting impacts. This research was conducted in October 2021 in batik SMEs located in North Sangatta District, East Kutai Regency. The basic method used in this research is descriptive analysis, which is a problem-solving procedure that is investigated by describing or describing the current state of the object of research in accordance with the facts obtained in the field. The